2017
DOI: 10.1007/s13246-017-0535-5
|View full text |Cite
|
Sign up to set email alerts
|

Expert system classifier for adaptive radiation therapy in prostate cancer

Abstract: A classifier-based expert system was developed to compare delivered and planned radiation therapy in prostate cancer patients. Its aim is to automatically identify patients that can benefit from an adaptive treatment strategy. The study predominantly addresses dosimetric uncertainties and critical issues caused by motion of hollow organs. 1200 MVCT images of 38 prostate adenocarcinoma cases were analyzed. An automatic daily re-contouring of structures (i.e. rectum, bladder and femoral heads), rigid/deformable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Out of the 75 retrieved papers, 49 can be categorized as data-driven decision support approaches 1058 . As regards to the addressed task, a large part of these contributions deals with prediction, intended as classification or regression 1015 , 1719 , 21 – 36 , 3842 , 4446 , 48 , 49 , 5254 , 57 . One work is focused on association rule mining 20 , and one adopts statistics for risk analysis 55 .…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 75 retrieved papers, 49 can be categorized as data-driven decision support approaches 1058 . As regards to the addressed task, a large part of these contributions deals with prediction, intended as classification or regression 1015 , 1719 , 21 – 36 , 3842 , 4446 , 48 , 49 , 5254 , 57 . One work is focused on association rule mining 20 , and one adopts statistics for risk analysis 55 .…”
Section: Resultsmentioning
confidence: 99%
“…A further substantial improvement in delineation precision can finally be expected from using multimodality images in the same atlas (potentially on an integrated treatment platform such as the MR-LINAC) and machine learning approaches, as they are already being implemented and tested at various points along the RT treatment planning chain [34][35][36]. Machine learning could, in a first step for the software platform used here, be used to eliminate the manual intervention in the hierarchical clustering approach.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an expert system based on machine learning technic was developed to address dosimetric uncertainties caused by motion of hollow organs (e.g. rectum, bladder) for prostate cancer radiation therapy (Guidi et al 2017). These limited but innovative studies have demonstrated the great potential of employing RSDM for rectum dose-toxicity relationship analysis.…”
Section: Introductionmentioning
confidence: 99%